2010
DOI: 10.1007/s00134-010-1785-9
|View full text |Cite
|
Sign up to set email alerts
|

Are home ventilators able to guarantee a minimal tidal volume?

Abstract: The six home ventilators tested in the study were able to maintain a minimal tidal volume during an increase in airway resistance and a decrease in lung compliance, but not during a non-intentional leak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 21 publications
2
40
0
Order By: Relevance
“…The ability of a home ventilator to maintain a stable V T is related to the pressurization capacities of the device, 126 as well as to its assessment of V T , especially in the presence of leaks. 127 One study showed that 4 of 6 devices designed to maintain a preset V T tended to underestimate V T . 127 Also, all but one of these devices failed to maintain a preset V T in the presence of unintentional leaks.…”
Section: Built-in Ventilator Softwarementioning
confidence: 99%
See 1 more Smart Citation
“…The ability of a home ventilator to maintain a stable V T is related to the pressurization capacities of the device, 126 as well as to its assessment of V T , especially in the presence of leaks. 127 One study showed that 4 of 6 devices designed to maintain a preset V T tended to underestimate V T . 127 Also, all but one of these devices failed to maintain a preset V T in the presence of unintentional leaks.…”
Section: Built-in Ventilator Softwarementioning
confidence: 99%
“…127 One study showed that 4 of 6 devices designed to maintain a preset V T tended to underestimate V T . 127 Also, all but one of these devices failed to maintain a preset V T in the presence of unintentional leaks. Furthermore, underestimation of V T increased significantly at higher pressure support levels.…”
Section: Built-in Ventilator Softwarementioning
confidence: 99%
“…Below we provide some brief information on sighs, mouth piece ventilation and modes of ventilation that switch from one control variable to another (e.g. from pressure to volume-targeted ventilatory support, so-called dual modes) [26,33,[43][44][45][46][47][48][49][50].…”
Section: Modes Of Ventilationmentioning
confidence: 99%
“…The physician/respiratory therapist must be aware that: 1) in the presence of modifications of respiratory impedance, VTG mode is able to guarantee a preset volume independently from circuit configuration [49]; 2) there are differences between VTG delivered by ''vented'' versus ''non-vented'' single limb respiratory circuits in presence of non-intentional leaks [24,50]; 3) when a patient's ventilatory demand produces a VT higher than the preset one, the patient is no longer supported. For this reason, the minimum value of the preset pressure should be carefully set by the operator.…”
Section: Recommendationsmentioning
confidence: 99%
“…PRVC is designed to adapt the amount of pressure to changes in respiratory impedance. However, theoretically, PRVC ventilation is not able to cope with unintentional leaks, especially when these leaks vary over time, 11 as with NIV via mouthpiece or ventilation via uncuffed tracheostomy tube. When unintentional leaks occur during pressure control ventilation, the inspiratory flow delivered by the ventilator increases to reach the target inspiratory airway pressure, whereas the tidal volume decreases.…”
Section: Evaluation Of the Patients' Equipment Versus The Prescribersmentioning
confidence: 99%